Componentes do ciclo celular ao longo da gênese do melanoma e seus possíveis reguladores - Cruz, Adriana Taveira da [UNIFESP] (2010)
Epigenetic studies regulatory mechanisms of the activity and inheritance in gene expression that is independent of modifications in the nucleotide sequence. The main epigenetic events are: DNA methylation and histone pos-translational modifications. miRNAs are non-coding RNAs that bind to mRNA targets and disturb their stability and/or translation, thus acting in the post-transcriptional regulation. It is estimated that over 30% of mRNAs are regulated by miRNAs and therefore these molecules are considered essential in the processing of many biological responses, such as cell proliferation, apoptosis and stress responsiveness. Changes in the epigenetic machinery like modifications in miRNA expression profile can modify the expression of cell cycle components. Some studies suggest that cancer is also a disease of cell cycle. In this regard the aim of the present study was identify the contribution of cell cycle components in melanoma genesis and their possible regulators. For that it was used a murine model of melanoma genesis in which several cell lineages were obtained after submitting melan-a melanocytes to sequential cycles of anchorage blockade. Significant alterations were identified in expression of the cell cycle components, p53, p21, cyclin D1 and cdk4 along melanocyte malignant transformation. It was observed loss of p53 expression in the same time that was observed an increase in expression of p21 in the aggressive melanoma lineages. It was also observed alterations in the expression of dnmt1 during the genesis of melanoma. Protein immunoprecipitation assays showed that p53 interact with dnmt1 only in melan-a melanocytes. Twenty five miRNAs were found differentially expressed along the process of malignant transformation and the miRNAs 138, 340-5p, 678 and 330 were recognized as possible regulators of p53, cyclin D1, Cdk4 and p21, respectively. These data show the contribution of epigenetic and miRNA machinery in the regulation of cell cycle and the importance of the equilibrium of these pathways in maintenance of cell phenotype. Cell cycle components imbalance are involved in malignant transformation of melan-a melanocytes and epigenetic machinery might contribute to these alterations. The therapeutic targets that focus on epigenetic machinery could be useful interventions against cancer. Besides that, the p53 protein interacts with one of the major components of the epigenetic machinery, dnmt1. This indicates that the components of cell cycle may regulate this enzyme and contribute for the maintenance of DNA methylation pattern. The miRNAs identified also represent strong candidates in the contribution of melanoma genesis. They may be useful as therapeutic targets on interventions against cancer.